Kolaborasi antara Masyarakat dan Mahasiswa KKN UNPAND dalam Membangun Ketahanan Pangan melalui Urban Farming di Kelurahan Pakintelan, Kecamatan Gunungpati, Semarang - Mutiawati Mandaka; Sharfina Bella Pahleva Wahyono; Tri Susetyo Andadari; Gatoet Wardianto (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
Urban farming in Pakintelan Village, Gunungpati District, Semarang, was initiated to overcome food security challenges and improve local economic welfare through the use of limited land in urban areas. The main problem faced is the low level of community participation in agricultural activities and a lack of understanding of sustainable agricultural practices. This program involves UNPAND KKN students in providing training in farming techniques, organic pest management, and the use of compost fertilizer. The methods applied include direct training and mentoring by extension workers, routine monitoring and evaluation, and outreach through local communities. Apart from that, the program also encourages the processing of harvests into value-added products and the formation of small farmer groups to strengthen community involvement. As a result, this program has succeeded in increasing community participation, maintaining environmental sustainability, and contributing to the economy with the potential to use harvests for consumption or sale. It is hoped that the replication of the program in other areas will expand its impact, making urban farming a sustainable and inclusive model of urban agriculture.